Influence of Calcination on Different Properties of Sugarcane Bagasse and Waste Ash - Sultana, M. S.; Rahman, M. A.; Zaman, M. N.; Ahmed, A. N. (Journal of Scientific Research, 2015)
Sugarcane bagasse is a fibrous waste product and important biomass sources, which is used as a fuel in the sugar industry. Bagasse ash is an industrial waste that mainly consists of high amount of silica and carbon materials. In this study sugarcane bagasse ash (SCBA) and sugarcane waste ash (SCWA) were calcined at 400°C, 600°C, 800°C and 1000°C for 2 h. These samples were characterized in order to evaluate the possibility of their use in different industries. XRF and XRD analyses were done for chemical and phase analysis of both calcined samples. The chemical composition of calcined SCBA and SCWA indicated that samples had similar compositions of other pozzolanic material. Carbon content has been determined by elemental analyzer. With increasing temperature the percentage of carbon content decreases in both cases. As temperature increases, the color of SCBA and SCWA samples changing from black to grey and white, which also indicates that the carbon content present in the SCBA were reasonably reduced. XRD patterns showed that crystallinity increases with influence of calcining temperature for both ash samples.